Using the Patient Concerns Inventory in the identification of fatigue following treatment for head and neck cancer. Issue 7 (July 2021) - Rogers, S.N.; Semple, C.J.; Humphris, G.M.; Lowe, D.; Kanatas, A.
Abstract: Fatigue has a profound impact on health-related quality of life (HRQOL). The aim of this study was to describe the clinical characteristics and HRQOL of head and neck cancer patients who raised the issue of fatigue on the Patient Concerns Inventory (PCI) at their review consultation. Eight consultants were randomized to use the PCI as part of a cluster-controlled trial. Patients also completed the University of Washington Quality of Life version 4 (UWQOL), EQ-5D-5L (EuroQol Group), and Distress Thermometer questionnaires. The study included 140 patients who attended clinics at a median of 108 (interquartile range 70–165) days after the end of treatment. The PCI item 'fatigue' was the sixth most commonly selected, by 29% ( n = 40). Those with advanced tumours were more likely to have selected the item (30/84, 36% vs 10/56, 18%; P = 0.02), as were those treated with radiotherapy ± chemotherapy (34/87, 39% vs 6/53, 11%; P < 0.001). The PCI fatigue group reported significantly worse overall quality of life, social–emotional and physical function composite scores (UWQOL), Distress Thermometer, and EQ-5D-5L. PCI fatigue was common in those with sleeping, nausea, mood, depression, mobility, breathing, and energy level concerns. In conclusion, given the problems associated with fatigue, it is appropriate to screen and seek interventions that might help patients address this.